Do We See It the Same Way? Event Perception in ADHD: Description and Links to Social Impairments - Ryan, Julia (Université d'Ottawa / University of Ottawa, 2019)
Attention-Deficit/Hyperactivity Disorder (ADHD) is associated with functional impairments across the lifespan, including in the social domain. The cognitive processes underlying the disorder, as well these associated social impairments, are still being debated. This points to the need for introducing new approaches. Event perception, the process of perceiving ongoing streams of activity into whole events, provides a unique perspective on the cognitive and social deficits in ADHD and how they might be related. Event perception is a compelling approach due to its methodological advantages, theory, and originality. Therefore, the overarching goal of this dissertation is the use of event perception to elucidate cognitive underpinnings of ADHD and associated social impairments. In the background section of this dissertation, I review the evolution of scientific conceptualizations of ADHD as a disorder and its core features, including cognitive underpinnings. In addition, I highlight the cognitive components of the disorder, revealing a need for continued exploration of possible cognitive contributors. Next, I deliver an overview of the functional impairments associated with ADHD, with a special focus on social difficulties. Current theories regarding the factors that contribute to social impairment among those with ADHD are presented along with their methodological, conceptual and practical shortcomings. To address these flaws, I propose turning to event perception as a mechanism of social cognition. This section ends with a description of the guiding Event Segmentation Theory, links between event perception and ADHD, and potential event perception related contributions to the ADHD literature. The first study addresses event perception as a cognitive deficit among those with ADHD, while the second addresses the relationship between event perception, symptoms of ADHD, and social functioning. Results of the two studies point to event perception differences associated with ADHD, as well as symptoms of ADHD acting as mediators in the relationship between event perception and social impairment. As a first initiative to apply event perception to ADHD and its related impairments, these results contribute to current conceptualization of ADHD, as well as support the use of event perception to further inquiries into ADHD and development of future interventions. The dissertation is concluded with a broad discussion of the meaning of the results, as well as limitations, implications and future research directions.
Keywords: ADHD; social perception; Event perception; cognition